Centring Complex Maternal Emotion in The Babadook - Pyles, Tessa (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
Jennifer Kent’s horror film The Babadook shines a spotlight on maternal ambivalence, which is easily read as horrifying in a culture that demands mothers feel or express nothing but love for their children. However, Kent asks her audience to look beyond maternal ambivalence as a representation of bad, mad, or monstrous mothering and instead as an act of resistance to one of the most intimate forms of female oppression—motherhood. Read this way, The Babadook challenges what Adrienne Rich named the "institution of motherhood." I argue that The Babadook moves beyond the institution of motherhood and into the realm of the emotional and psychological ramifications the institution engenders. I engage Barbara Almond’s The Monster Within: The Hidden Side of Motherhood to help convey the experiences of what she refers to as "the dark side of motherhood." It is in this dark space that Amelia, the film’s protagonist, finds herself. Like so many mothers, Amelia has no outlet to honestly express what and how she feels about motherhood and about her child. As a result, she denies and represses her feelings. But monsters are not often born from the expression of feelings but from their repression, and the more her feelings are denied the stronger the monster—the Babadook—grows. Ultimately, The Babadook challenges the many cultural and emotional restrictions placed upon mothers. More so, it asks those of us who are mothers to consider loving and maybe even nurturing the monster within.